Perceived Effectiveness of Government Preventive Measures as Predictor of Attitude and Acceptance toward COVID-19 Vaccines - Ronel Dagohoy (Journal of Government and Political Issues, 2022)
A positive attitude toward the COVID-19 vaccine and increased vaccination uptake made the institutions behind these efforts realize their goal of creating an immune community. This research would provide crucial information on how the government can establish a desirable attitude of people toward COVID-19 vaccines through their responses to the adversities of the pandemic. This study assessed government preventive influence measures 'perceived effectiveness on the citizens' attitudes and acceptance toward the COVID-19 vaccines. The researchers used descriptive-correlational quantitative design and simple regression analysis as research methods. The study was conducted in the City of Panabo, with 384 samples chosen randomly and surveyed through an adapted instrument. The findings of this study revealed that both the levels of perceived effectiveness of government preventive measures and attitudes toward the COVID-19 vaccine were high, while acceptance of the COVID-19 vaccine was only average. The perceived effectiveness of government preventive measures and attitudes and acceptance toward the COVID-19 vaccine have a positive, high and significant relationship. It further revealed a significant influence manifested between the variables of the study. The effectiveness of government preventive measures is an essential factor in influencing citizens' attitudes and acceptance toward the COVID-19 vaccines. When the government implements preventive measures more influential, the higher the confidence in manifesting a positive attitude and good acceptance of the COVID-19 vaccines. Government and local health authorities will be served with assistance in promoting vaccination in the country and strengthening the preventive protocols implemented to control the rapid spread of the COVID-19 disease.